Sustainable Higher Education via Telecollaboration: Improving Plurilingual and Pluricultural Competence - Oksana Polyakova; Ruzana Galstyan-Sargsyan (National Research Mordova State University, 2021)
Introduction. Due to globalisation, the modern workforce is significantly diversified. Therefore, there is a need to modernise and embrace innovation in 21st-century education to prepare international professionals to work in cross-cultural teams via digital platforms. While research in the recent past has primarily focused on the refinement of future expert competences in tertiary education, only a handful of studies have been done to establish how plurilingual and pluricultural competence can be digitally developed at the inter-university level. In this light, this study sought to bridge this gap in the research on the sustainable cooperation model. Materials and Methods. The design for the methodological plan of integrating plurilingualism and pluriculturalism in university teaching was premised on the need to promote networking among students from different universities and countries. Its major stages based on the Collaborative Online International Learning approach included three stages: find a partner, prepare the project and carry out the project. A virtual exchange experiment across two institutions of higher learning in Spain and Finland helped analyse plurilingual and pluricultural competence achievement by means of questionnaires. Results. A special Collaborative Online International Learning approach used to explore plurilingual and pluricultural competence and the effectiveness of online-assisted language interaction, teamwork or intercultural cooperation. The study's findings confirmed that plurilingual and pluricultural competence among students could also be developed using virtual cooperation, thus supporting cost-effective options of sustainable university training. Discussion and Conclusion. The project had a positive impact on reaching sustainable education goals by highlighting intercultural interaction prospects. Besides, it displays real challenges such as different schedules, grading systems, timing, motivation or virtual interaction among learners and ways of overcoming them. Regardless of the fundamental idea of formative exploration, our study presents some findings that lecturers, language training practitioners and policymakers willing to apply telecollaboration will be deserving of thought.